Peran Lembaga Alternatif Penyelesaian Sengketa Perbankan Indonesia (LAPSPI) dalam Penyelesaian Sengketa Pembiayaan di Bank Syariah - Ramadhani, Tengku Rahmah; Brawijaya, Andri; Aziz, Imam Abdul (Sharia Faculty Islamic Economic Law Study Department, 2021)
The purpose of this study was to determine the Role of the Indonesian Banking Dispute Resolution Alternative Institution (LAPSPI) in Financing Dispute Resolution at Islamic Banks and the dispute settlement process at LAPSPI. The method used is a qualitative descriptive method using content analysis. The data sources used are primary data and secondary data. Based on the results of research related to the role of the Indonesian Banking Dispute Resolution Alternative Institution (LAPSPI), it cannot be used as the main choice in assisting the settlement of problematic financing disputes because it does not have executive power and the decision is a peace agreement. The settlement process at LAPSPI is divided into 3 (three), namely mediation, adjudication and arbitration